PERBANDINGAN Perbandingan Alokasi Belanja Negara (Studi Komparasi Era Rasulullah dan Khulafaurrasyidin dengan Era Pemerintahan Joko Widodo Periode 2014-2019) - Abdul Wahab (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2019)
Activities that increase state expenditure have a certain impact on people's socio-economic lives. A leader must be able to meet the needs of his people, the main needs such as food, clothing, housing, health, education, security, welfare, etc., through a policy made by a head of state. The Islamic state government no longer needs to make (new) types of expenditures and renewals every year, because the chapters and their explanations have been determined directly by Allah, and also do not need to seek public approval (through their representatives in the DPR) on the matter. This will be very different from a democratic (non-Islamic) country such as Indonesia, which determines the types of revenues and expenditures through people's decisions (DPR), and is done through voting. From the results of the literature study, it was concluded that the equation of the allocation of state expenditure, namely: (1) Infrastructure Development and Connectivity, (2) Provision of Health and Social Welfare Services, (3) War and Security Fleet Development, and (4) Education Movement. While the differences are: (1) Spread of Islam, (2) Scope of Baitul Maal Activities, (3) Distribution of Assistance and Village Funds, (4) Providing Allowances (5) Implementation of Democratic Agenda, and (6) Anticipation of Uncertainty (Alert Fund).